Ars cantus mensurabilis mensurata per modos iuris = The Art of Mensurable Song Measured by the Modes of Law - Balensuela, Matthew (Lincoln and London University of Nebraska Press, 1994)
An anonymous fourteenth-century treatise that borrows heavily from the Libellus cantus mensurabilis attributed to Johannes de Muris, the Ars cantus mensurabilis mensurata per modos iuris differs from others ars nova treatises in its systematic application of scholastic philosophy and allusions to medieval law. Using music as the subject of inquiry, the writer addresses questions that occupied scholastic philosophers in other fields, such as the natural minimum of a substance and the potentia Dei absoluta. The writer quotes legal maxims and alludes to medieval legal issues such as the lex regia and the Becket controversy to justify and prove the rules of music.A substantial portion of the treatise was first published as Anonymous V in Edmond de Coussemaker's Scriptores de musica medii aevi, where it was paired with a counterpoint treatise beginning "Cum notum sit". The treatise published by Coussemaker, however, is not the entire work. From textual and manuscript evidence, the Greek and Latin Music Theory edition demonstrates that a set of three figures and an introduction are related to the mensural treatise; the same evidence suggests that the counterpoint treatise "Cum notum sit" should not be considered part of the treatise.The GLMT edition of the anonymous fourteenth-century treatise presents a complete critical text for the treatise together with a facing-page English translation. Annotations to the translation explain the numerous legal and scholastic allusions in the treatise. Also presented are corrected versions of the approximately one hundred musical figures. Preceding the critical text and translation, an extended introduction explains the musical and intellectual sources of the work.
A new critical text and translation on facing pages, with an introduction, annotations, and indices verborum and nominum et rerum by C. Matthew Balensuela
Keywords: Middle Ages (500-1400); Vocal music; Method; Europe